STEM-06. A DRAFT SINGLE-CELL ATLAS OF HUMAN GLIOBLASTOMA REVEALS SPATIAL AND DIFFERENTIATION GRADIENTS OF STEM-LIKE CELLS. (5th November 2018) - Mueller, Soeren; Bhaduri, Aparna; DiLullo, Elizabeth; Yagnik, Garima; Lim, Daniel; Aghi, Manish; Kriegstein, Arnold; Diaz, Aaron
Abstract: Glioblastoma (GBM) stem-like cells (GSCs) expressing markers of the proneural (e.g. OLIG2, DLL3) and mesenchymal (e.g. CHI3L1(YKL-40), CD44) GBM molecular-subtypes have been described. However, it is unknown if these two GSC types are sufficient to generate the spectrum of cellular heterogeneity observed in GBM. The spatial localization and niche interactions of GSCs have not been fully elucidated. We perform single-cell RNA-sequencing (scRNA-seq) and matched exome sequencing of human GBMs from a cohort of 21 patients, profiling over 40, 000 cells. We combine in silico lineage tracing and meta-analysis of public data to identify recurrent cellular hierarchies of GSCs and their progeny. We map GBM cells to tumor-anatomical structures using reference atlases. We perform immunofluorescence staining and automated image analysis on a cohort of 300 human GBMs using markers of GSC lineage and phenotype to visualize and quantify niche interactions. Proneural GSCs (pGSCs) upregulate markers of cell-cycle progression and PDGF signaling compared to mesenchymal GSCs (mGSCs). By contrast, most mGSCs have a quiescent phenotype, but overexpress cytokines responsible for the chemotaxis of myeloid-derived suppressor cells (e.g. CSF1, CCL2, PTGS2). We find cycling mGSCs enriched in the perivascular space and quiescent mGSCs enriched in hypoxic regions, pGSCs are enriched in the tumor's invasive edge. Increased mGSC content, but not increased pGSC content correlates with significantly inferior survival in TCGA data. All clonal expressed-mutations in our biopsies are found in the GSC populations, with a greater representation of mutations in mGSCs. We conclude that varying proportions of mGSCs and pGSCs, their progeny and stromal/immune cells are sufficient to explain the genetic and phenotypic heterogeneity observed in GBM. Moreover, pGSCs and mGSCs aggregate in distinct tumor compartments, display different rates of proliferation and distinct niche interactions. Intratumor heterogeneity is a barrier to targeted therapeutics. This study sheds light on the heterogeneity of GSCs in vivo.